Perbandingan Perilaku Seksual Menyimpang dalam Novel Nayla dengan Novel Tabularasa - Caterine, Reni Claudia; Asri, Yasnur; Nst., M. Ismail (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research are: 1) describing the kinds of behavior of sexual digress in Nayla novel masterpiece of Djenar Maesa Ayu with Tabula Rasa novel masterpiece of Ratih Kumala, 2) describing factor of causing behavior of sexual digress in both of novel, 3) describing analogies and differences of behavior of sexual digress in both of novel. The datum collect by descriptive method the following research finding. The first, kinds of behavior of sexual digress in the both of novel are homosexual (lesbian and gay), pedophilia. The second, factor of causing behavior of sexual digress in the both of novels are psychologycal, sociocultural, and education and family factor. The third, analogies and differences behavior of sexual digress in both of novels are 1) analogies are homosexual (gay), obscenity, masturbation, and adultery. Aspect personality of dominant figure in Nayla novel is ego while Tabula Rasa is id.